Breach of contract: an Indonesian experience in akad credit of sharia banking - Ayup Suran Ningsih; Hari Sutra Disemadi (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2019)
This research aims to determine and analyze the implementation of the concept of profit-sharing in Islamic banking credit agreements based on regulations in force in Indonesia and also to find out and analyze defaults undertaken by customers in Islamic banking credit agreements. The method used in this research is normative juridical, which is a method that puts forward secondary data in the form of primary, secondary and tertiary legal materials. The secondary data in question such as Law Number 21 of 2008 concerning Sharia Banking, related books, and legal research journals. This research is based on the high community needs for capital to achieve the objectives of a business into a separate phenomenon. The concept of muamalah on the teachings of Islam that Muslims want to adhere to is one of the reasons for the birth of the concept of Islamic banking in Indonesia. The concept of profit sharing is one of the concepts known in Islamic banking. The risk of breach of contract by the customer is a necessity.